THE EDUCATION OF CHARACTER BASED ON LOCAL WISDOM: A QUALITATIVE STUDY OF THE GAYO COMMUNITY OF CENTRAL ACEH - Bahri, Syamsul; Musanna, Al (Jurnal Review Pendidikan dan Pengajaran, 2023)
It is believed that the spread of various social illnesses among the students is the result of a lack of attention to the character education of the students. Today, the practice of character education has been enriched by the emergence of the idea of articulating local wisdom as its basis. The revitalization of local wisdom in educational practice is motivated by the belief that modernity with all its supporting tools is not enough to guide human beings to achieve a meaningful life. The modern educational praxis that is currently developing widely and is oriented towards economic and political demands has marginalized local values and culture, so that schools also play a significant role in alienating students from their socio-cultural context. The idea of developing local wisdom-based education is based on the belief that every community has a strategy for living life according to its context. The Gayo people have strategies and local wisdom guiding their people in leading their lives. This qualitative study will answers to the following questions: (1) What is the profile of the local wisdom of the Gayo community? (2) What aspects of the local wisdom of the Gayo community can be used as a basis for developing a character education model? The research specifically aims to describe the profile of the existence of local wisdom of the Gayo community in the current context; efforts to identify aspects of local wisdom of the current Gayo community that are considered relevant in developing character education; and formulating a conceptual model character education based on the local wisdom of the Gayo community.